2024
DOI: 10.3389/fpsyt.2023.1281847
|View full text |Cite
|
Sign up to set email alerts
|

The impact of problematic mobile phone use and the number of close friends on depression and anxiety symptoms among college students

Wei Wang,
Huiqiong Xu,
Shuqin Li
et al.

Abstract: BackgroundPsychological problems often occur in college students, with the most common ones being depression and anxiety symptoms. Exploring the risk factors that influence depression and anxiety symptoms in college students is essential to promote their physical and mental health.ObjectiveThis study aimed to investigate the independent and interaction effects of problematic mobile phone use (PMPU) and the number of close friends (NCFs) on depression and anxiety symptoms and the comorbidity of these symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…More recently, a study also pointed out that problematic mobile phone use was an important risk factors for depression. 18 Significantly, a previous investigation also highlighted that as sitting hours accumulate, university students experience a significant rise in depression and anxiety. In line with the social withdrawal hypothesis, this phenomenon could be attributed to the increased viewing of television or use of computers and the internet, which in turn fosters a sedentary lifestyle and reduces social interactions.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, a study also pointed out that problematic mobile phone use was an important risk factors for depression. 18 Significantly, a previous investigation also highlighted that as sitting hours accumulate, university students experience a significant rise in depression and anxiety. In line with the social withdrawal hypothesis, this phenomenon could be attributed to the increased viewing of television or use of computers and the internet, which in turn fosters a sedentary lifestyle and reduces social interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, a higher quality of interpersonal relationships can lead to lower levels of anxiety and stress (17). Furthermore, longitudinal studies have found that the level of interpersonal relationships among college students can directly predict their levels of depression (18,19). Additionally, there is evidence to suggest a link between diet and negative emotions.…”
Section: Introductionmentioning
confidence: 99%